Optimizing toughness, ductility, and sustainability in strain-hardening cementitious composites: The synergistic effect of ultrafine palm oil fuel ash - M. Altwair, Nurdeen; M. Al-Tayeb, Mustafa; Putra Jaya, Ramadhansyah; M. Alsharif, Abdualhamid (Elsevier Ltd, 2026)
This study investigates the effects of incorporating 1.60 µm ultrafine palm oil fuel ash (POFA), thermally treated at 400°C, into strain-hardening cementitious composites (SHCC). The physicochemical and morphological characteristics of the ultrafine POFA were analyzed through microstructural techniques. Different SHCC matrices without polyvinyl alcohol (PVA) fibers with w/b ratios ranging from 0.16 to 0.24 and varying ultrafine POFA substitution levels (0 %, 15 %, 25 %, 30 %, 35 % and 45 % by volume) were evaluated for flowability, compressive strength, and fracture behavior. The tensile properties of PVA-reinforced composites were investigated via uniaxial tensile tests at a w/b ratio of 0.22, with ultrafine POFA contents of 0 %, 15 %, 25 %, 35 %, and 45 %. Economic and environmental impacts were quantified using Material Sustainability Indicators (MSIs). Results demonstrate that ultrafine POFA treated at 400°C meets Class N pozzolan standards, with desirable chemical properties and thermal stability. Incorporating ultrafine POFA enhances fiber-free SHCC flowability and compressive strength, with optimal performance at 15–25 % replacement levels; exceeding this reduces strength. Higher w/b ratios decrease fracture properties, while 15 % ultrafine POFA maximizes fracture stress and toughness. Optimal POFA (15 %) boosts initial and ultimate tensile strength; higher contents increase tensile strain capacity up to 3.4 times and refine crack widths (50–85 μm). High-volume ultrafine POFA (45 %) in SHCC reduces costs and environmental impact, achieving a carbon footprint comparable to or better than normal concrete, positioning it as a sustainable alternative.